P233 Cough swabs should not be used to exclude non-tuberculous mycobacterial (NTM) infection in adults with cystic fibrosis. (12th November 2015) - Brown, C; Choyce, J; Rodgers, N; Rashid, R; Whitehouse, JL; Smith, EG; Nash, EF
Abstract : Introduction and objectives: People with cystic fibrosis (CF) are prone to airway infection with non-tuberculous mycobacteria (NTM) including M. abscessus, M. avium and M. intracellulare . Routine NTM screening is recommended for all patients at least once a year. 1 In patients not able to produce sputum, cough swabs are often sent for NTM analysis. Anecdotally, we observed that several patients cared for in our centre had cultured NTM in sputum having previously been culture-negative from cough swabs. The objective of this observational study was to examine the diagnostic yield of cough swabs and sputum samples from CF adults with known NTM infection. Methods: We identified all CF patients being cared for in our large regional adult CF centre that had cultured any NTM species from cough swabs or sputum samples and are currently attending our NTM clinic. Demographics, clinical parameters and microbiology results were recorded and analysed. Results: 26 patients (19 male) were included: median age 24 years, 92% chronically infected with P. aeruginosa, 100% pancreatic insufficient, 62% CF-related diabetes, 27% ABPA. 381 sputum samples and 55 cough swabs were analysed. 251 (66%) sputum samples and 4 (7%) cough swabs cultured NTM (see Table 1). In the 4 cough swabs that cultured NTM, sputum samples also cultured the same species. Conclusions: Cough swabs have a very low diagnostic yield and their use did not contribute to identification of NTM infection in our adult CF patient population. We have therefore stopped sending cough swabs for NTM culture in our centre and our data suggests that cough swabs should not be used to screen for these organisms. Reference: 1 Mycobacterium abscessus Suggestions for infection prevention and control. CF Trust, 2013